Clinical impact of tropism testing in a real-life cohort of HIV infected patients: a retrospective observational study - Laurène Deconinck (BMC Infectious Diseases, 2019)
Abstract Background The circumstances of prescription of tropism tests clinically relevant in treatment-experienced patients are unclear. Methods We performed a monocentric retrospective analysis of all tropism tests performed between 2006 and 2015 in HIV-infected patients on antiretroviral therapy (ART) without MVC. The motivation of tropism determination was collected. Factors associated with MVC prescription were determined using logistic regression analysis. Results Five hundred sixty-three tests were performed in experienced patients not receiving MVC. Reasons for tropism performance were: virological failure (44%), side effects or drug-interactions (37%), simplification or sparing strategies (11%), immunological failure (5%), and improvement of neurological diffusion (3%). MVC was prescribed in 110 cases (20%), though 366 tests (65%) revealed a tropism CCR5. MVC was more often prescribed before 2011 (OR 3.65, 95% CI 2.17–6.13) and in patients with multiple previous ART regimens (less than 4 ART regimens compare to more than 10 ART regimens (OR 0.34, 95% CI 0.15–0.74)). Conclusions In experienced patients not receiving MVC, tropism test prescription should be restricted to patients with virological failure and limited therapeutic options such as patients already treated with a wide range of ART regimens.